The Hidden Forces Behind Employee Citizenship Behavior: Kekuatan Tersembunyi di Balik Perilaku Kewarganegaraan Karyawan - Palupi, Dian; Setyabudi, Teguh Gunawan; Tegowati (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to investigate the direct and indirect effects of perceived organizational support on work engagement and organizational citizenship behavior (OCB). A sample of 60 employees from a clinical laboratory in East Java was examined using a quantitative approach with probability sampling. Data was collected through online questionnaires and analyzed using SmartPLS 3.0 software. The findings reveal that 1) perceived organizational support significantly influences work engagement, 2) work engagement has a significant positive impact on OCB, and 3) perceived organizational support directly affects OCB. Additionally, work engagement mediates the relationship between perceived organizational support and OCB. These results highlight the importance of fostering organizational support to enhance work engagement and citizenship behavior, providing practical insights for improving employee commitment and performance.